2005
DOI: 10.1182/blood-2005-03-0944
|View full text |Cite
|
Sign up to set email alerts
|

Sequential activation of class IB and class IA PI3K is important for the primed respiratory burst of human but not murine neutrophils

Abstract: It is well established that preexposure of human neutrophils to proinflammatory cytokines markedly augments the production of reactive oxygen species (ROS) to subsequent stimuli. This priming event is thought to be critical for localizing ROS to the vicinity of the inflammation, maximizing their role in the resolution of the inflammation, and minimizing the damage to surrounding tissue. We have used a new generation of isoform-selective phosphoinositide 3-kinase (PI3K) inhibitors to show that ROS production un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
275
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(304 citation statements)
references
References 53 publications
28
275
1
Order By: Relevance
“…These various results, which were apparently contradictory, suggest that both class I A and class I B PI3Ks are activated following fMLP stimulation. Moreover, a recent study using a series of PI3K isoform-specific inhibitors has provided evidence for a sequential activation of class I B and class I A in response to fMLP in TNF-␣-primed neutrophils (31). Although the latter study did not examine the direct effects of the chemotactic factor, the data provided also support the idea that multiple isoforms of PI3Ks are required for chemoattractant-stimulated PI(3,4,5)P 3 production.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…These various results, which were apparently contradictory, suggest that both class I A and class I B PI3Ks are activated following fMLP stimulation. Moreover, a recent study using a series of PI3K isoform-specific inhibitors has provided evidence for a sequential activation of class I B and class I A in response to fMLP in TNF-␣-primed neutrophils (31). Although the latter study did not examine the direct effects of the chemotactic factor, the data provided also support the idea that multiple isoforms of PI3Ks are required for chemoattractant-stimulated PI(3,4,5)P 3 production.…”
Section: Discussionmentioning
confidence: 82%
“…Direct activation of p110␤ by G␤␥ has been described (32,33), and this mechanism could account in part for the activation of PI3K I A by fMLP. Different lines of evidence suggest that nonreceptor tyrosine kinases, such as the Src family tyrosine kinases, could be involved in the activation of PI3K by chemotactic factors (20,31). We also observed that PP2, an inhibitor of the Src family tyrosine kinases, significantly reduced the accumulation of PI(3,4,5)P 3 in fMLP-stimulated neutrophils (our unpublished data), suggesting that this family of enzymes is implicated in the regulation of the PI(3,4,5)P 3 response to the chemotactic agent.…”
Section: Discussionmentioning
confidence: 99%
“…In the latter cells, stimulation with the chemotactic peptide fMLP caused a rapid activation of p38 MAPK, Erk, and PI3K. Interestingly, inhibition of p38 MAPK and PI3K, but not Erk, resulted in a drastic reduction of ROS formation and neutrophil chemotaxis (42)(43)(44)(45)(46)(47). Noteworthy, PF4 activates in human neutrophils neither PI3K nor p38 MAPK and is indeed unable to induce ROS release or chemotaxis in these cells (19,21,48).…”
Section: Discussionmentioning
confidence: 99%
“…Cells can indeed detect differences in the concentration of chemoattractant between points on their surface (41) and translate the extracellular gradient into an intracellular derivative, encoded by the signaling networks engaged by the chemoattractant. Localized accumulation of PI3Ps is a critical signal coordinating chemotaxis or movement and depends on PI3K␥ and SHIP-1 (31,40,42). The study of Chen et al (6) proposed that ATP released from developing leading edges can act to control chemotaxis.…”
Section: Discussionmentioning
confidence: 99%